Arctic bacterial diversity and connectivity in the coastal margin of the Last Ice Area - Girard, Catherine; Vincent, Warwick F.; Culley, Alexander (Nature Publishing Group, 2023)
Arctic climate change is leading to sea-ice attrition in the Last Ice Area along the northern coast of Canada and Greenland, but less attention has been given to the associated land-based ecosystems. Here we evaluated bacterial community structure in a hydrologically coupled cryo-ecosystem in the region: Thores Glacier, proglacial Thores Lake, and its outlet to the sea. Deep amplicon sequencing revealed that Polaromonas was ubiquitous, but differed genetically among diverse niches. Surface glacier-ice was dominated by Cyanobacteria, while the perennially ice-capped, well-mixed water column of Thores Lake had a unique assemblage of Chloroflexi, Actinobacteriota, and Planctomycetota. Species richness increased downstream, but glacier microbes were little detected in the lake, suggesting strong taxonomic sorting. Ongoing climate change and the retreat of Thores Glacier would lead to complete drainage and loss of the lake microbial ecosystem, indicating the extreme vulnerability of diverse cryohabitats and unique microbiomes in the Last Ice coastal margin.